Stickler syndrome: exploring prophylaxis for retinal detachment - Coussa, Razek Georges; Sears, Jonathan; Traboulsi, Elias I (Current opinion in ophthalmology, 2019)
The literature regarding prophylactic treatment of rhegmatogenous retinal detachment in Stickler syndrome remains controversial. We review major published clinical studies and offer a critical analysis of this subject. Stickler syndrome is a systemic collagenopathy affecting multiple organ systems including the eye, ear, and skeleton. Stickler syndrome is probably the most common cause of genetically determined pediatric rhegmatogenous retinal detachment. Congenital developmental anomalies constitute over half rhegmatogenous detachments (RRD) in patients less than 10 years. The majority are caused by hereditary vitreoretinopathies associated with Stickler syndrome. Sixty percent of patients with Stickler syndrome develop RRD's over their lifetime with possible severe visual loss and subsequent lifelong morbidity. In view of these complications, some have emphasized the importance of prophylactic laser treatment to the retina of patients with Stickler syndrome to reduce the occurrence of and/or prevent future rhegmatogenous retinal detachment, but there appears to be insufficient data to support the absolute benefit of such prophylactic treatment. Guidelines regarding the age at prophylactic treatment as well as type and frequency of intervention are scarce and would benefit from additional clinical investigations.